Evaluation of some natural water-insoluble cellulosic material as lost circulation control additives in water-based drilling fluid - Ahmed Mohamed Alsabagh; Mahmoud Ibrahim Abdou; Hany El-sayed Ahmed; Ahmed Abdel-salam Khalil; Amany Ayman Aboulrous (Egyptian Journal of Petroleum)
Circulation losses have always been a serious and expensive problem to the drilling industry. Even with the best drilling practices circulation losses do occur. In order to reduce such losses to acceptable level fluid Loss Control Material (LCM) is used. In this work, three natural water-insoluble cellulosic materials; peanut hulls, bagasse and sawdust were investigated as lost circulation control materials. One hundred and eight different LCM samples made of various materials were tested with mud. The experiments were conducted in a permeability plugging apparatus (PPA) at a differential pressure of 100 psi and 300 psi, using 10, 60 and 90 ceramic discs. The performance of each LCM sample was determined based on the amount of spurt loss and total fluid loss of the mud according to the American Petroleum Institute (API) standard. The obtained results showed that, the amount of the fluid loss depends on the LCM material, concentration and size distribution, testing results show that, the peanut gives the best results among the bagasse and sawdust, especially fine size which exhibited better results in the filtration characteristics due to the better filling properties of this size. Peanut hulls, bagasse and sawdust show a slight effect on the rheological properties of the mud. The results were discussed on light of particle size distribution.